Image Visualization and Mechanical Measurements on Biocompatible Glass Ionomer Restorative Cement - Altinawi, Amir (British Journal of Healthcare and Medical Research, 2023)
The present study aimed to corroborate image visualization techniques with mechanical measurements on biocompatible glass ionomer restorative cement of different compositions. Commercially available biocompatible glass ionomer restorative cement (BGIRC) was mixed with Arabic Gum (AG) powder with different weight percentages (0, 0.5, 2, 4, & 8). Mean and variance values were measured for image visualization. Additionally, diametral tensile strength and compressive strength tests were used to measure the mechanical properties. T-test and Tukey’s post hoc tests were used to find any statistical significance among the data. The findings revealed that mean values for the image visualization technique displayed the same pattern as diametral and compressive strength tests and their values. The mean values also displayed a significant difference between the groups with different wt.% of AG powder when mixed with BGIRC. Image visualization parameter i.e. mean values and mechanical testing i.e. diametral tensile strength surfaced a method in emphasizing the properties of the BGIRC with AG. Although the diametral tensile strength test is a more reliable method for identifying the mechanical properties of BGIRC with AG, image visualization displays a factual evaluation of the material.